CODE SWITCHING IN THE ENGLISH CLASS ACTIVITY IN THE SUBJECT “ENGLISH FOR A GROUP ACTIVITY” IN ENGLISH EDUCATION STUDY PROGRAM, UNIVERSITY OF BANTEN JAYA BANTEN - Hendra Hendra (Journal of English Language Teaching and Literature (JELTL), 2018)
Code-switching is a phenomenon that exists in bilingual societies where people have the opportunity to use two or more languages to communicate. Being able to speak more than one language, bilinguals can code-switch and use their languages as resources to find better ways to convey meaning. Code-switching occurs in English Study Program, Faculty of Lecturer Training, University of Banten Jaya, Serang, Banten. Therefore, the aim for this paper was to investigate when and why the lecturer in the class “English for a Group Activity” used code-switch when teaching L2 English. It has also looked into what language the learners preferred in different classroom situations. Alecturer were interviewed and 32learners taking the class. The results showed that the lecturer generally tried to code-switch as little as possible but that they did code-switch in some of those situations where the learners preferred either a combination of Bahasa Indonesia and English or only Bahasa Indonesia. Two of these situations were grammar instructions, where a majority of the learners preferred a combination of English and Bahasa Indonesia, and one-to-one situations, where a majority of the learners preferred Bahasa Indonesia.